Traces of coloniality in narratives of music graduates: (auto)biographical approaches as a bridge between life experiences and training (Orfeu, 2023)
This article aims to present partial data from a master's research that analyzed the influence of institutionalized and non-institutionalized music education environments on the training of students in a music degree course at a university in the North of the country, from the perspective of the students themselves. The research that originated such data covered (auto)biographical theoretical-methodological assumptions and was designed from a narrative construction inspired by educational and music-educational biography. The study of this biographical material was carried out based on Discourse Analysis, in which were considered traces of coloniality present in the research participants' discourses that seem to hinder dialogues and musical creations from a counter-hegemonic perspective. In order for this difficulty to be minimized, there is a need for a bridge between musical experiences that occurred in different musical learning spaces, which can be accomplished through the exploration of (auto)biographical methodologies in training contexts.
Keywords: music education; degree in music; (auto)biographical research